2021
DOI: 10.1177/02734753211041743
|View full text |Cite
|
Sign up to set email alerts
|

The Pedagogy of Vulnerability and Marketing Education: Cultivating Self-expansion in a Time of Separation

Abstract: Applying the pedagogy of vulnerability and self-expansion theory, the exercise known as the Know Me Activity (KMA) enhances self-expansion by encouraging connections between students and the instructor. The pedagogy of vulnerability is premised on risking self-disclosure as an act of courage. Self-expansion theory is grounded in personal relationships whereby individuals are motivated for personal growth and identify with others to gain access to their resources. In the context of marketing education, self-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…When viewed through the lens of self-determination theory, this study demonstrated how relatedness and competence differed for marketing educators in their motivation to attend a particular academic conference virtually or in-person. Prior marketing education studies have considered student perceptions regarding instructor relatedness and competence (Jillapalli & Wilcox, 2010; Syrdal et al, 2021). This is the first study to consider these motivations for faculty professional development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When viewed through the lens of self-determination theory, this study demonstrated how relatedness and competence differed for marketing educators in their motivation to attend a particular academic conference virtually or in-person. Prior marketing education studies have considered student perceptions regarding instructor relatedness and competence (Jillapalli & Wilcox, 2010; Syrdal et al, 2021). This is the first study to consider these motivations for faculty professional development.…”
Section: Discussionmentioning
confidence: 99%
“…The motivation has to do with one's sense of internal control versus being controlled by external factors (Ryan et al, 2021). Thus, autonomy does not have application to all motivation situations as reflected in prior studies in higher education (Fedesco et al, 2019) and marketing education in particular (Jillapalli & Wilcox, 2010;Syrdal et al, 2021). Moreover, individuals are not restricted in their decisionmaking when it comes to academic conference attendance.…”
Section: Self-determination Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Novice students were given a survey near the end of the semester. The three-item scale from Syrdal et al (2021) was utilized to capture perceived effectiveness of CCPG as a course component. A five-item scale adapted from Colquitt (2001) measured distributive justice.…”
Section: Methodsmentioning
confidence: 99%
“…I feel prepared to critique the work of colleagues in a professional setting. (Syrdal et al, 2021) Perceived effectiveness I recommend using peer grading in the course in the future.…”
Section: Sourcementioning
confidence: 99%